Lesbian modernism : - English, Elizabeth (Edinburgh critical studies in modernist culture, 2017)
Explores the aesthetic dilemma prompted by the censorship of Radclyffe Hall's novel The Well of Loneliness in 1928. Faced with legal and financial reprisals, women writers were forced to question how they might represent lesbian identity and desire. Modernist experimentation has often been seen as a response to this problem, but English breaks new ground by arguing that popular genre fictions offered a creative strategy against the threat of detection and punishment. Her study examines a range of responses to this dilemma by offering illuminating close readings of fantasy, crime, and historical fictions written by both mainstream and modernist authors.--Provided by publisher